Endoparasite diversity and zoonotic risk in wild-caught Javan spitting cobra (Naja sputatrix) from Indonesia - RYANKA EDILA; MUSTOFA HELMI EFFENDI; LUCIA TRI SUWANTI; HYUCK-KEUN KWON; JOHN YEW HUAT TANG; SAIFUR REHMAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Edila R, Effendi MH, Suwanti LT, Kwon H-K, Tang JYH, Rehman S. 2025. Endoparasite diversity and zoonotic risk in wild-caught Javan spitting cobra (Naja sputatrix) from Indonesia. Biodiversitas 26: 4146-4156. The Javan spitting cobra (Naja sputatrix) is widely used in Indonesia for food and traditional medicine, creating potential zoonotic risks from parasitic infections. This study aimed to assess the diversity and prevalence of endoparasites in wild-caught N. sputatrix purchased from local sellers in Sidoarjo, East Java, Indonesia. Fifty-one snakes were examined through necropsy, coprological, and blood smear analyses. Parasitic infection was detected in 82.3% (42/51) of snakes, with mixed infections predominating across all age groups. A total of ten parasite taxa were identified, including nematodes (Capillaria, Kalicephalus, Strongyloides, Ophidascaris), cestodes (Spirometra), acanthocephalans (Sphaerechinorhynchus), pentastomids (Porocephalus), intestinal protozoa (Balantidium, Eimeria), and a hemoparasite (Hepatozoon). Notably, zoonotic species such as Spirometra spp. (54.9%), Porocephalus spp. (11.76%), and Ophidascaris spp. (7.84%) were prevalent, underscoring public health threats associated with snake consumption and handling. This is the first comprehensive parasitological survey of N. sputatrix in Indonesia and the first host record of Porocephalus in this species. Findings highlight the ecological role of cobras as reservoirs of zoonotic parasites and emphasize the need for One Health surveillance to mitigate cross-species transmission risks. The study also contributes baseline data for wildlife trade monitoring, biodiversity conservation, and public health policy related to human-snake interactions in Southeast Asia.